Optimization of Logistics Inventory Management in Enterprises from the Supply Chain Perspective - Jiang, Xiuhua (International Journal of Global Economics and Management, 2024)
For enterprise logistics inventory management, it also brings greater challenges and opportunities. The traditional enterprise logistics inventory management is relatively decentralized and independent, so from this point of view, it is difficult to achieve overall economic benefits in the process of operation. So, from this point of view, under the perspective of the supply chain, through the continuous optimization and integration of the enterprise’s logistics inventory, so as to improve the quality and efficiency of its warehousing, to meet the actual needs of the enterprise, which is also a prerequisite and basis for improving the core competitiveness of modern enterprises in the fierce market competition. This paper describes the current situation of inventory management in logistics enterprises, analyses the inventory management problems of logistics enterprises, and puts forward the management path under the supply chain perspective, with a view to promoting and improving the development of enterprise inventory management under the supply chain management environment.